Studi Literatur: Bagaimana Akuntansi Mempengaruhi Pengelolaan dan Optimalisasi Pajak dalam Perusahaan - Andri Suwendi; Rizqy Hizbullah Ziyaulhaq; Sulthon Ahmad; Gina Sakinah (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study is a literature review aimed at examining how accounting influences the management and optimization of taxation within companies. The review focuses on four main aspects: the basic concepts of tax accounting, the role of accounting in tax optimization, the relationship between tax accounting and taxpayer compliance, and tax risk management through accounting. Tax accounting functions as a strategic tool to help companies understand and apply tax regulations appropriately. Through accurate financial recording and reporting, companies can optimize their tax burdens legally and efficiently. In addition, sound accounting practices promote higher levels of tax compliance and assist in identifying and managing tax risks that could harm the company. Thus, accounting plays an important role in establishing effective, efficient, and sustainable tax governance in modern business practices.